Analysis of the influence of social media marketing and customer relationships on intention to purchase hand sanitizer products - Gromyko Bongso; William Jayadi; Vera Dumonda Silitonga (Jurnal Mantik, 2023)
This research analyzes the medical equipment industry which focuses on hand sanitizers, with the aim of analyzing the relationship between social media marketing and customer relationships on consumer purchase intention for hand sanitizer products and brands. The analytical method used in this research is the quantitative method. Based on the results of distributing questionnaires to 124 respondents, 80 respondents were obtained who met the research criteria. Then the data obtained is processed using the SmartPLS 3.0 application. As a result of data processing, it was found that social media marketing and customer relationships had a positive and significant effect on purchase intention. It can be concluded that the company's focus is on online marketing to increase consumer buying interest in hand sanitizer.